Pelatihan Kewirausahaan Dan Pengelolaan Keuangan Bedasarkan Standar Akuntansi Keuangan (SAK) Bagi UMKM Di Desa Pagerharjo, Samigaluh, Kulon Progo - Bambang Sugeng; Jemadi Jemadi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The SME empowerment policy is generally directed at supporting efforts to overcome poverty and inequality, create job opportunities and increase exports, as well as agricultural and rural revitalization, which are national development priorities. In addition, the development of small and medium enterprises (MSMEs) is directed at making a significant contribution to creating job opportunities, increasing exports and increasing competitiveness.This Community Service Activity (PKM) is focused on MSMEs in Pagerharjo Village, Kulon Progo Regency. The reason for choosing this service location is because Pagerharjo Village is an Independent Cultural Village which has implemented the Preneur Village program since 2019. The Preneur Village is currently still active and developing. The problem with MSMEs, under the management of BUMDes Binangun Pagerharjo in Pagerharjo Village, Samigaluh, Kulon Progo Regency, is the lack of entrepreneurial spirit and financial bookkeeping which, on average, is still done manually.The results of the service include responses and evaluations from participants regarding the training that has been provided. The response was given by the Director of BUMDes who was impressed with the training provided which was different from the training that had been provided previously. Previous training involved mostly listening to lectures, whereas the current training involves participants being active in solving the various problems they face. The evaluation results show that the participants' knowledge has increased and their insight into their business has also increased. It turns out that producing a business is not only based on generations, but also requires innovation so that marketing will continue to develop and financial management will also improve.